Human Vγ9Vδ2-T Cells Synergize CD4+ T Follicular Helper Cells to Produce Influenza Virus-Specific Antibody - Chen, Qingyun; Wen, Kun; Lv, Aizhen; Liu, Ming; Ni, Ke; Xiang, Zheng; Liu, Yinping; Tu, Wenwei (Frontiers in Immunology, 2018)
Human Vγ9Vδ2-T cells recognize nonpeptidic antigens and exert effector functions against microorganisms and tumors, but little is known about their roles in humoral immune response against influenza virus infection. Herein, in the coculture of autologous human B cells, dendritic cells and/or naïve CD4 T cells and Vγ9Vδ2-T cells, we demonstrated that Vγ9Vδ2-T cells could facilitate H9N2 influenza virus-specific IgG and IgM productions in a CD4 T cell-dependent manner. Vγ9Vδ2-T cells promoted the differentiation of CXCR5+PD1+CD4+ Tfh cells, CD19+IgD-CD38++ plasma cells, and drove B cell proliferation as well as Ig class switching. Interestingly, Vγ9Vδ2-T cells acquired Tfh-associated molecules such as CXCR5, PD1, CD40L, and ICOS during influenza virus stimulation, especially in the presence of CD4 T cells. Moreover, Vγ9Vδ2-T cells promoted CD4 T cells to secrete IL-13 and IL-21, and neutralizing IL-13 and IL-21 significantly reduced the number of CD19+IgD-CD38++ plasma cells. Using humanized mice, we further demonstrated that Vγ9Vδ2-T cells could synergize CD4 T cells to produce influenza virus-specific antibody. Our findings provide a greater scope for Vγ9Vδ2-T cells in adaptive immunity, especially for the Tfh development and humoral immune responses against influenza virus infection.